2019
DOI: 10.1002/hyp.13528
|View full text |Cite
|
Sign up to set email alerts
|

Assessing DOC export from a Sphagnum‐dominated peatland using δ13C and δ18O–H2O stable isotopes

Abstract: Dissolved organic carbon (DOC) originating in peatlands can be mineralized to carbon dioxide (CO 2 ) and methane (CH 4 ), two potent greenhouse gases. Knowledge of the dynamics of DOC export via run-off is needed for a more robust quantification of C cycling in peatland ecosystems, a prerequisite for realistic predictions of future climate change. We studied dispersion pathways of DOC in a mountain-top peat bog in the Czech Republic (Central Europe), using a dual isotope approach. Although δ 13 C DOC values ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Others have shown that great WTD before a rain event favour rapid DOC mobilization and lead to greater exports, independently of the recurrence between events in a peatland (Birkel et al, 2017;Blaurock et al, 2021). The amount of exported DOC is also controlled by production processes, stimulated by the temperature (Clark et al, 2007(Clark et al, , 2009Grand-Clement et al, 2014;Zhu et al, 2022) because DOC concentrations in the peat pore water increase with the temperature (Freeman et al, 2001;Buzek et al, 2019). Among the studies that have used an event-based approach in peatland streams, most of them have been performed in temperate (Worrall et al, 2008;Austnes et al, 2010;Grand-Clement et al, 2014;Tunaley et al, 2016) and alpine (Birkel et al, 2017;Rosset et al, 2020) catchments, and none have been realized in boreal environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that great WTD before a rain event favour rapid DOC mobilization and lead to greater exports, independently of the recurrence between events in a peatland (Birkel et al, 2017;Blaurock et al, 2021). The amount of exported DOC is also controlled by production processes, stimulated by the temperature (Clark et al, 2007(Clark et al, , 2009Grand-Clement et al, 2014;Zhu et al, 2022) because DOC concentrations in the peat pore water increase with the temperature (Freeman et al, 2001;Buzek et al, 2019). Among the studies that have used an event-based approach in peatland streams, most of them have been performed in temperate (Worrall et al, 2008;Austnes et al, 2010;Grand-Clement et al, 2014;Tunaley et al, 2016) and alpine (Birkel et al, 2017;Rosset et al, 2020) catchments, and none have been realized in boreal environments.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have highlighted that long periods between rainfall events favour DOC production. Greater DOC exports are measured once the hydrological connection is restored, given the large amounts of DOC recently produced in the peatland and which could be mobilized through lateral discharge (Worrall et al, 2008;Clark et al, 2009;Grand-Clement et al, 2014;Buzek et al, 2019). Others have shown that great WTD before a rain event favour rapid DOC mobilization and lead to greater exports, independently of the recurrence between events in a peatland (Birkel et al, 2017;Blaurock et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the wetland showed more obviously depleted δ 13 C values than the river; however, the groundwater downstream of the wetland had the most depleted δ 13 C values (Figure 5). Jiangsa wetland is an important carbon reservoir that can produce a large amount of soil biogenic CH 4 and CO 2 (Bridgham et al, 2006; Buzek et al, 2019; Roulet, 2000). CH 4 is characterized by strong 13 C depletion (δ 13 C = −44‰ to −60‰) in the alpine wetland of the southern QTP (Kato et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our results considered the hypothesis about DOC downward movement. Numerous studies have analyzed DOC export from peatlands (Freeman et al, 2001;Frey and Smith, 2005;Buzek et. al., 2019;Blueten et al, 2020) but only few are related to the downward DOC movement and none covers this process in peatlands of Western Siberia, except (Schulze at al., 2015).…”
Section: Discussionmentioning
confidence: 99%